Analysis of the Effectiveness of Using Autodesk Revit Applications in Increasing Work Productivity: a Case Study of the Construction of the Al-Multazam Islamic Boarding School Building, Kuningan - Ahmad Syarif Hidayat; Faizal Adi Wibowo; Wahyu Nur Fadilah; Ohan Farhan (Riviera Publishing, 2024)
The implementation of construction work, there are still many problems, namely schedule mismatches, delays, and cost calculations that are sometimes inaccurate because they still use conventional methods. In the Al-Multazam Islamic Boarding School Building Construction project, Kuningan still uses traditional methods, where this method has the potential for human error because in making calculations it can be wrong to enter data which will ultimately change the calculation results to be greater. This research aims to show that the BIM method is very important to be applied in construction projects to streamline work productivity in building construction projects. In this case, there are differences in the results of the calculation of Quantity Take Off on the project, the difference in the results of the analysis shows that there is a difference between the existing volume and the volume of the Quantity Take Off results using the BIM concept, Foot plate foundation work has an average difference of 6.67%, Tie Beam has a difference of 7.62%, Beams have a difference of 5.30%, Columns have a difference of 8.26%, and Floor Plates have an average difference of 2.51%. This research has implications for the application of BIM to enable a more structured, efficient, and accurate planning and implementation process, thereby reducing the potential for errors caused by human factors. In addition, the use of BIM can also increase efficiency in overall project management, including in schedule monitoring, cost estimation, and resource management, which in turn can increase work productivity on building construction projects.